The Potential of MiRNAs as Biomarkers and Therapy Targets for Cancer - Teresa L. Wargasetia (Journal of Medicine and Health, 2016)
MicroRNAs (miRNAs) are involved in the signaling circuits regulation within a cell andtheir deregulation plays an important role in cancer development and progression. In thisreview, we discussed miRNA biogenesis, miRNA function and the effect of miRNA abnormalitiesin cellular pathways that led to transformation of normal cells into cancer cells, as well as theindication of miRNAs as diagnostic and prognostic biomarkers of various types of cancer, asbiomarkers to predict the response to cancer therapy and the potential for development ofmiRNAs as cancer targeted therapy.Keywords: miRNA, cancer, diagnostic biomarker, prognostic biomarker, cancer therapy